ChemInform Abstract: Reaction of Arylmethylidene Derivatives of 3H‐Furan‐2‐ones with Azomethine Ylide. Issue 13 (March 2016) - Anis'kov, Alexander A.; Kamneva, Irine Ye.; Zheleznova, Maria A.; Yegorova, Alevtina Yu.
Abstract: The title 1, 3‐dipolar cycloaddition procedure leads diastereoselectively to the previously unknown dispiropyrrolidine derivatives (IV) via an endo‐transition state.